Removal of filling material using rotating or reciprocating systems with or without solvent: microCT analysis - Bárbara Maria BIS; Yara Teresinha Corrêa SILVA-SOUSA; Luciana Martins Domingues de MACEDO; Orestes Pereira OLIVEIRA; Edson ALFREDO; Graziela Bianchi LEONI; Fuad Jacob Abi RACHED-JUNIOR (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract This study evaluated by the efficacy of rotary and reciprocating systems to remove filling material by micro-CT. Sixty human canines were instrumented up to F3 by ProTaper Universal system and filled with AH Plus/ gutta-percha. Specimens were submitted to 1,200 thermal cycles, scanned by microCT SkyScan 1176 and randomly distributed in groups according to the filling material removal protocol (n = 10): ProTaper Universal, ProTaper Universal/xylol, ProTaper Next, ProTaper Next/xylol, Reciproc and Reciproc/xylol. After filling removal, specimens were analyzed by microCT to separately verify the presence of gutta-percha and sealer remnants. The data (mm3) were analyzed by two way ANOVA and Tukey´s test (5%). For the remaining gutta-percha, the use of xylol provided the highest values for Reciproc (7.60 ± 0.73), which was statistically different from the other groups (p < 0.05) that presented lower values and were statistically similar to each other (p > 0.05). For the remaining sealer, xylol provided the highest values (21.25 ± 6.94) different (p < 0.05) from the use of instruments alone (11.47 ± 9.45). ProTaper Next presented the lowest values (8.16 ± 1.37) for the remaining sealer, different (p < 0.05) from that of Reciproc (24.67 ± 6.32). The qualitative analysis revealed that all groups presented some remaining root filling material, with the highest volumes presented by Reciproc and Reciproc/xylol. In conclusion the rotary systems provided greater removal of filling material regardless of the use of xylol. The use of xylol negatively interfered with the action of the reciprocating system in the removal of the gutta-percha and sealer.